Analysis of the Effect of School Counseling Services, Social Support, and Learning Motivation on Academic Achievement of Junior High School Students in West Java - Mokodenseho, Sabil; Mamonto, Riani; Mamonto, Irsan; Makalalag, Indra Wati; Zakaria, Siti Fatimah (Jurnal Psikologi dan Konseling West Science, 2024)
This quantitative study investigated the effect of school counseling services, social support, and learning motivation on the academic achievement of junior high school students in West Java, Indonesia. Data were collected from 120 students using standardized surveys, and structural equation modeling (SEM) with Partial Least Squares regression (PLS) was used for data analysis. The results showed a significant positive relationship between school counseling services, social support, learning motivation, and academic achievement. Specifically, school counseling services, social support, and learning motivation were found to positively predict academic achievement among junior high school students. In addition, mediation analysis revealed the indirect effects of these factors on academic achievement through intermediate variables. These findings highlight the importance of a comprehensive support system in driving student success and have implications for education stakeholders looking to improve academic outcomes in West Java and beyond.